Beyond Essentialism and Complementarity: Toward a Theological Anthropology Rooted in Haecceitas - Horan, Daniel P. (Theological studies, 2014)
The field of theological anthropology has experienced something of an impasse in recent decades as a result of the critical challenges that have arisen from developments in feminist theory and poststructuralist philosophy. This article explores the possibility that an approach to theological reflection on the human person rooted in the philosophical and theological innovations of John Duns Scotus in the development of his principle of individuation (haecceitas) can offer new resources for avoiding the pitfalls of essentialism and complementary.